Temporal changes in the physical fitness of Chinese adolescents aged 13-18 years: an analysis of eight national successive surveys over three decades - Ruan, Hui; Tang, Ruolan (Frontiers in Public Health, 2024)
Objective The aim of this study was to assess temporal changes in physical fitness of Chinese adolescents aged 13–18 years from 1985 to 2019. Methods Body size /composition and physical fitness indicators, including body height, weight, body mass index (BMI), speed, power, flexibility, muscular endurance, and cardiorespiratory fitness (CRF), were selected from Chinese boys and girls aged 13–18 years from eight Chinese National Surveillance on Students’ Constitution and Health from 1985 to 2019. Temporal changes in means were estimated by sample-weighted linear regression at the test × sex × age level, and national trends were estimated by a post-stratification population weighting procedure. Results Overall mean body height, weight and BMI increased significantly for Chinese adolescents over 34 years. There was a small improvement for boys in speed (Effect size [ES] = −0.21, 95% confidence interval [CI] = −0.44 ~ 0.02), a small improvement for boys in power (ES = 0.24, 95% CI = −0.20 ~ 0.69), a small improvement for girls in flexibility (ES = 0.45, 95% CI = 0.15 ~ 0.76), a moderate decline for boys (ES = -0.53 95% CI = −0.84 ~ −0.21) and a moderate improvement for girls (ES = 0.61, 95% CI = −0.03 ~ 1.26) in muscular endurance, and large declines in cardiorespiratory fitness (CRF) for boys (ES = 0.93, 95% CI = 0.64 ~ 1.21) and girls (ES = 0.93, 95% CI = 0.58 ~ 1.27) from 1985 to 2019. These trends in each component of fitness were more positive for adolescents aged 13–15 years than that of adolescents aged 16–18 years in both sexes, except for girls in flexibility. Conclusion The decline in CRF was most pronounced among Chinese children and adolescents from 1985 to 2019, suggesting a future decline in population health that needs attention.